Нigh-current ion beam compensation in a section of an induction linac - Karas’, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2018)
The particle transport dynamics in the section of a linear induction accelerator (LIA) has been studied. The system and beams parameters (the magnetic field magnitude, the system dimensions, the beams parameters), which allowed compensating the ion beam in the entire LIA section are found. It is shown, that the high-current ion beam (HCIB) at the system output can be used in many technological applications.